ANALISIS PENGARUH PEMBERIAN INSENTIF TERHADAP KINERJA KARYAWAN PADA PT. ISTANA DELI KENCANA MEDAN - Purba, Betniar (UNIKA Santo Thomas, 2019)
The purpose of this study was to find out and analyze the effect of giving incentives on employee performance at PT. Deli Kencana Palace Medan, for the development of science, especially in the field of human resource management, as a reference in conducting further research for the development of science, especially in the field of human resource management, as a reference in conducting further research. The research population is incentives and the number of vehicles serviced by employees of PT. Deli Kencana Palace Medan from 1983-2016. The research sample was taken in 2016. The data collection techniques used were documentation techniques. The data analysis technique used is simple linear regression. From the results of the research and discussion obtained a simple linear regression equation is Y = 515,462 + 0,033X. That is, giving incentives has a positive effect on employee performance at PT. Medan Deli Kencana Palace. This can be seen from the regression coefficient which is positive. The value of the correlation coefficient (R) is 0.693, meaning that giving incentives has a fairly strong and positive relationship to the performance of employees at PT. Medan Deli Kencana Palace. The determinant coefficient (R2) is 0.481. That is, employee performance can be explained by giving incentives of 48.1% while 51.9% is explained by other factors. Judging from the z test, the z calculated value is 7.574 with a significance level of 0.000